Influence of varietal selection and treatments on the nutritive value of selected pulse crop residue - Alkhtib, A.S. (Jimma University, 2017)
The current study was aimed to analyze the utilization of crop residue in the mixed farming systems of Ethiopia, to explore the possibility of improving straw yield and nutritive value of chickpea, faba bean and lentil without compromising grain yield and to identify the effect of dung and wood ash treatments on the nutritive value of chickpea, faba bean and lentil straw. Data on crop residue production and utilization was collected in two highland regions of Ethiopia from 160 households. To assay the varietal variation and food-feed relation in faba bean, 4 improved and released variety and one local variety were planted at the Sinana Agricultural Research Center, Ethiopia during 2014-2015 cropping season. To evaluate the variability in grain yield and straw traits in chickpea and lentil, 24 improved varieties and one local variety of each crop were replicated four times in a randomized complete block trial in two locations of Debre Zeit Research Center during the 2013-2014 cropping season. Straw from plots of the local varieties of the trials was used to determine the effect of 4% urea treatment, dung ash treatment (0g ash/L, 100 g ash/L, 200 g ash/L 300 g ash/L) and wood ash treatment (0 g ash/L, 150 g ash/L, 200 g ash/L) on the nutritional value. All straw samples were analyzed for proximate analysis, in vitro organic matter digestibility and metabolizable energy using a combination of Near Infrared Reflectance Spectroscopy and conventional feed analyses methods. Results showed that farmers prefer using crop residue from pulses over crop residue from cereals for livestock feeding purposes. Proportions of cereal and pulse residue used for soil mulch was positively affected by education level of the farmer, distance between homestead and cultivated land, extension service, awareness about soil mulch, slope of cultivated land, participation in farmer-to-farmer extension and crop residue generated in the preceding season. The proportion of crop residue from pulses that was used as feed was positively affected by education level of the farmer, livestock extension service, number of small ruminants and crop residue stack from the previous season. The effect of the variety, location and variety-location interaction on grain yield, straw yield and straw nutritive value was significant in chickpea and lentil. The correlation between grain yield and straw traits of chickpea was weak in all locations. Grain yield of lentil correlated weakly to crude protein and ME in Chefe Donsa while it correlated moderately to crude protein in Zebre Zeit. Grain and straw yields were positively, strongly and significantly correlated in faba bean. Grain yield of faba bean correlated weakly to the nutritive value parameters of straw. Varietal variations in grain yield, straw yield and straw quality traits within its fractions were significant. The botanical structure of faba bean straw can be used as a reliable method for screening faba bean genotypes for straw quality. Urea treatment showed potential to improve the nutritive value of chickpea, faba bean and lentil straw. Dung ash treatment up to 300 g ash/L and wood ash treatment up to 200 g ash/L did not improve the nutritive value of chickpea, faba bean and lentil straw. Integrating straw yield and nutritive value into improvement programs of chickpea, faba bean and lentil could improve the nutrients supply for livestock and increase the amount of cereal straws allocated to soil mulching.